Design and experimental investigation of a new photoelectrochemical reactor for green hydrogen production. (16th January 2023) - Karaca, Ali Erdogan; Dincer, Ibrahim
Highlights: A new photoelectrochemical reactor is developed for hydrogen production. Cu2 O photoelectrode with unique geometry is fabricated by electrodeposition process. The performance of the reactor concept is experimentally investigated. Abstract: The current study undertakes the development, experimental testing and performance evaluation of a new photoelectrochemical reactor for green hydrogen production. The reactor is uniquely designed to utilize the available solar light more effectively. A copper oxide photocathode fabricated by the electrodeposition technique is employed as a photoelectrode in the reactor. As a counter electrode, the reactor comprises a titanium dioxide-coated electrode offering high stability in the presence of moisture and corrosive media. The electrochemical tests of the reactor are experimentally conducted for various conditions to better evaluate the performance, including with light and without light conditions. In this regard, both energy and exergy efficiencies of the present reactor for hydrogen production rates are evaluated under various operating conditions. The results of the current study show that the highest hydrogen production rate from the reactor is found to be 0.62 µg/s with a solar irradiation intensity of 600 W/m 2 and an applied voltage of 2.0 V and that the present reactor achieves an energy efficiency of 0.193% and an exergy efficiency of 0.196% under these conditions.